Black Flag's My War Side Two: Cultural and Aesthetic Legacies in Studio Recording. Issue 4 (8th August 2021) - Carter, David; Rogers, Ian
ABSTRACT: In 1984, L.A. punk band Black Flag released My War . Coming three years after Damaged – a canonized classic of the hardcore genre – and following a period of legal dispute and touring hiatus, My War was diverse and polarizing; side two of the album featured three slow, long riff-heavy songs that run counter to the predominantly lean and fast signature sound of the band's previous work and that of many contemporaries. With the benefit of hindsight, these tracks signaled punk's reinvestment in heavy metal, precipitating new hybrid forms such as sludge metal, drone metal, and stoner metal. In this paper, we exhume a subset of this aesthetic lineage and discuss how it has informed a subsequent recording: Lysol by theMelvins. Through analysis of recorded works, we demonstrate how the sounds of side two of My War have been propagated and refined, highlighting the links between these idiosyncratic sounds and the pragmatic realities of low-budget studio production.